Emotional intelligence and problem solving skills in individuals who attempted suicide - Korkmaz, Sevda; Keles, Denizhan Danaci; Kazgan, Asli; Baykara, Sema; Gurok, Mehmet Gurkan; Demir, Caner Feyzi; Atmaca, Murad (Elsevier Sci Ltd, 2020)
Aim: Based on our clinical observations, low emotional intelligence level and problem-solving skills may have play a role in suicide attempts. The present study is aimed to investigate the emotional intelligence levels and the correlation between problem solving skills and suicide attempts in individuals who already attempted suicide. Material and method: The study was conducted on twenty-five individuals who attempted suicide and 25 healthy controls with similar sociodemographic characteristics. All participants were asked to fill in the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Problem-Solving Inventory (PSI) and Emotional Intelligence Scale (EIS). Findings: It was determined that the patient group BAI scores and BDI scores were significantly higher when compared to the control group (p < 0.01, p < 0.01). The total EIS and emotional awareness, emotion management, self-motivation, empathy and relationship control subscale scores of the patient group were significantly lower when compared to the control group (p < 0.01, p < 0.01, p < 0.01, p < 0.01, p = 0.047).PSI scores were significantly higher in the patient group when compared to the control group (p < 0.01). There was a negative correlation between PSI total score and EIS subscale scores. Conclusion: It was observed that these individuals experienced more difficulty in solving problems when compared to healthy individuals, however as their emotional intelligence levels increased, their problem-solving skills increased as well. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Suicide attempt; Emotional intelligence; Problem-solving; Anxiety; Depression